The Japanese Catheter Ablation Registry (J‐AB): Annual Report in 2023 - Kengo Kusano; Koichi Inoue; Koshiro Kanaoka; Koji Miyamoto; Yasuo Okumura; Yu‐Ki Iwasaki; Kazuhiro Satomi; Seiji Takatsuki; Kohki Nakamura; Seigo Yamashita; Masaharu Masuda; Yoshitaka Iwanaga; et al. (Journal of Arrhythmia)
ABSTRACT The Japanese Catheter Ablation (J‐AB) registry, started in August 2017, is a voluntary, nationwide, multicenter, prospective, observational registry performed by the Japanese Heart Rhythm Society (JHRS) in collaboration with the National Cerebral and Cardiovascular Center. From January 2022, the data registration system was changed from the Research Electronic Data Capture (REDCap) system to the Fountayn system. The purpose of this registry is to collect the details of target arrhythmias, the ablation procedures, including the type of target arrhythmias, outcomes, and acute complications in real‐world settings. During the year of 2023, we have collected a total of 102 584 procedures (mean age of 66.9 years and 65.2% male) from 549 participant hospitals. Detailed data were shown in figures and tables.